Соціально-демографічні процеси у Полтавській губернії під час Першої світової війни - Саранча, В. (Краєзнавство, 2016)
У статті розглянуто динаміку чисельності, склад і заняття населення Полтавської губернії
у 1914-1917 рр. Проаналізовано основні показники демографічної статистики регіону періоду Першої світової війни. The socialdemographic development aspects of the Poltava province in the years of First world
war are investigated in the article.
The lack of fundamental demographic statistics works of Large war predetermines actuality of regional
studios to index a quantity and composition of population of regions of Ukraine in this period.
The demographic processes and social structure of population of Poltava province during the war
are described In the article.
The dynamics of quantity, composition and employment of population of the Poltava province, is
considered in 1914-1917, the basic indexes of demographic statistics of region are analysed.
It is indicated that the First world war caused the appearance of negative demographic tendencies:
deceleration of increase rate of total population, reduction of birth-rate and amount of marriages.
Before the direct influence it is possible to take the change of a ratio of men and women that consisted
in noticeable reduction of masculine population of Poltava. At the same time it practically did
not influence on class proportions, did not result in the increase of death rate among citizens.
It is found out, that migratory processes resulted in the increase of level of urbanization. Due to the actual stopping of migration of population to East regions the positive dynamics of increase of population in Poltava province was saved. В статье рассмотрены динамика численности, состав и занятия населения Полтавской
губернии в 1914-1917 гг. Проанализированы основные показатели демографической статистики региона периода Первой мировой войны.